Associations of IL-12, IL12R polymorphisms and serum IL-12 levels with high-risk human papillomavirus susceptibility in rural women from Luohe, Henan, China. Issue 38 (September 2019) - Song, Jiayu; Zhang, Qingwei; Wang, Rong; Sun, Mingzhen; Jin, Shaoju
Abstract: Background: Interleukin 12 (IL-12) and interleukin 12 receptor (IL12R), key inflammatory cytokines in the immune system, participate in bridging the innate immunity and adaptive immunity. No previous work has reported the role of IL-12 and IL12R in high-risk human papillomavirus (hrHPV) susceptibility. The purpose of this study was to investigate the association of IL-12, IL12R polymorphisms, and serum IL-12 levels with hrHPV susceptibility in rural women from Luohe, Henan, China. Methods: Two hundred sixty cases with hrHPV infection and 260 healthy controls were selected. Enzyme-linked immunosorbent assays were used to detect the serum IL-12 levels, and the polymorphisms of IL12B rs3212227, IL12RB1 rs393548, and IL12RB1 rs436857 were determined using DNA sequencing. Results: The serum IL-12 levels were significantly lower in cases with hrHPV infection compared with those in healthy controls ( P  < .01).There was no significant difference in IL12 rs3212227, IL12RB1rs436857, and IL12RB1rs393548 genotype and allele frequencies between cases and controls ( P  > .05). Furthermore, with respect to the IL12 rs3212227 polymorphism with serum IL-12 levels, although serum IL-12 levels were lower in cases than in controls, we did not find any differences between serum IL-12 levels and genotypes in cases( P  > .05). Conclusions: Our data demonstrates that low serum IL-12 levels may be associated with hrHPV susceptibility but are not associated with IL-12 gene polymorphisms; furthermore, IL-12 and IL12R gene polymorphisms may not contribute susceptibility to hrHPV in rural women from Luohe, Henan, China.